Anti-Elite Politics and Emotional Reactions to Socio-Economic Problems. Experimental Evidence on 'Pocketbook Anger' from France, Germany, and the United States - Paul Marx (Institute of Labor Economics (IZA), 2019)
Many observers have noticed the importance of anger in contemporary politics, particularly with reference to populism. This article addresses the question under which conditions people become angry about a specific aspect of their lives: their personal financial situation. Specifically, it asks if populist anti-elite rhetoric has a causal influence on anger and if this influence differs across socio-economic groups. The theoretical expectation is that populist rhetoric allows people to externalize responsibility for an unfavorable financial situation and thereby to turn negative self-conscious emotions into anger. The argument is tested with original survey data from France, Germany, and the United States. The empirical analysis yields three main insights. First, negative emotional reactions to respondents' personal finances (and anger in particular) are surprisingly widespread in all three countries. Second, there is a pronounced socio-economic gradient in anger and other negative emotions. Third, and most importantly, randomly exposing participants to (mildly) populist anti-elite rhetoric causes considerably higher expressed anger about one's financial situation in France and Germany, but less so in the United States. This suggests a causal role of populist rhetoric in stirring 'pocketbook anger'. This is true in particular in the middle classes. The notion that populist rhetoric reduces negative self-conscious emotions, such as shame, is not supported by the data.
Keywords: D72; D74; P16; 330; populism; anger; socio-economic problems; middle class; survey experiments